Rights and responsibilities : - Sloan, Stephen (McGraw-Hill ESL/EST, 2004)
Rights and Responsibilities: Reading and Communication for Civics will greatly aid newcomers to the United States who must simultaneously learn English and adjust to American housing, work, school, finance, health, and political systems and practices. Each chapter skillfully combines practical information with activities that develop reading, vocabulary, and conversation skills as students learn how to establish banking credit, register to vote, use a library, and enroll children in schools and sports programs.